Evaluation of tendering effect from date seed extract (P. dactalytera) in knuckle part meat (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
Phoenic dactylifera (date) is a species of flowering plants in the family of Arecaceae. Date seeds are considered as a waste from many processing that produced plants pitted date, confectionery date syrup and date itself. Currently, the seeds are used mainly for animal feed in the cattle and chicken industry. In 2004, about 863,000 tonnes of date seeds are produced out of 6.9 million tonnes date. Tenderness is the major concern that affecting consumer acceptance of beef in meat industry. This study was carried out in order to investigate the effects of the bioactive compound extracted from date seed as a tenderizing agent in meat. Extraction of date seeds used a different method of extraction (Soxhlet and Maceration). The application of extracted on knuckle part of beef were performed and papain was used as a positive control and followed by the sensory evaluation. The analysis of cooked meat was performed in order to analyze the physico-chemical properties of date seeds extract. The result from the study revealed that the aqueous extract (maceration techniques) gave the best percentage of the total yield recovery with 28.44%. The physico-chemical properties of cooked meat showed the reducing of pH value after cooking. Meanwhile for the cooking yield, result showed that almost 86% of water losses during cooking for aqueous extract and positive control and 96% for negative control. According to the sensory evaluation of the cooked meat, scoring test and hedonic test were performed using One Way Anova. The result for texture is 6.10±2.1, juiceness is 5.87±1.76 and taste is 6.80±1.34. All attributes have no significant different at p
Keywords: date seeds; Phoenic dactylifera; knuckle part; tenderization agent